MERANCANG ULANG KOTA: LANGKAH ADAPTASI DALAM MENCIPTAKAN KOTA BERKELANJUTAN - Purwanto, Edi (Universitas Atma Jaya Yogyakarta, 2012)
Abstract: Currently, urban architecture is frequently referred to as one of main contributors for the occurrence of global warming. Global warming issue is getting more popular in which high-rise buildings in cities becomes one of the causes as they produce 68% of total CO2 emission gas on the earth. The emission of green house gasses in the year of 1970-2004 increased by 70%, global temperature increased by 0.72% in ten decades, and since 1961 the sea surface topography has increased by 0.175 cm/year. In other words, urban architecture greatly contributes in increasing micro climate, particularly city climate. The micro climate is caused by the heat emitted by buildings and roads, and building equipments using electrical energy. The finishing of architectural design in cities by using heat emitting materials tends to be environmentally unfriendly. The design has a potency to create climate disorder. The building mass, particularly high-rise buildings in the city area, is designed independently. Consequently, it reflects heat among building mass one another, and it disrupts shadowing system. Global warming effect is still neglected by architects. They still believe in the superiority of architectural design in technological context and anti-natural. The issues of global warming effect seem to be the central issues to be considered by architects and city designers on how important urban architectural design, which is environmentally friendly, in creating an environmentally responsive city. In addition, the effects of global climate change have to be redefined in the design criteria of urban architectural buildings. The result of this study shows that redesigning urban architecture has to consider some factors, such as technical finishing design using recent technology, people behaviour, and related regulations.Keywords: redesign, adaptation, sustainableAbstrak: Selama ini, arsitektur perkotaan seringkali dianggap sebagai salah satu penyumbang utama terjadinya pemanasan global (“global warming